Dynamic competitive constraint handling for constrained multi-objective optimization - Wei Li; Haoying Li; Ning Yang; Shuling Yang; Ying Huang (Swarm and Evolutionary Computation, 2026)

Legacy and emerging organophosphate compounds in plateau rivers: Insights into environmental fate and risk from target and nontarget analyses - Zhenfei Han; Jinze He; Yisheng Xu; Wei Zheng; Xuexin Yang; Shuling Duan; Song Tang; Xiaoyu Cui; Yindong Tong; Hongyang Cui (Environmental Research, 2026)

Effects and Mechanism of Lactobacillus gasseri CCFM1346 Combined with Rutin on Alleviating Hyperuricemia in Mice - Xin Tang; Shuling Zhang; Bingyong Mao; Qiuxiang Zhang; Jianxin Zhao; Wei Chen; Shumao Cui (Probiotics and Antimicrobial Proteins, 2026)

Chronic Fluoride Exposure from Brick Tea Consumption Disrupts Bone Remodeling and Contributes to Bone Loss in Chinese Population with Skeletal Fluorosis - Hongjiang Long; Yubo Liu; Pinggui Lei; Ting Hu; Zhijuan Shao; Yu Luo; Shuling Zhang; Jinshu Li; Peng Luo; Zhenting Zhang; Shaofeng Wei (Biological Trace Element Research, 2026)

Herbacetin alleviates acute doxorubicin cardiotoxicity via regulating the ERK1/2-FOXO3a signaling pathway - Sijia Bian; Xinran Li; Peiyan Zhu; Zhiting Jiang; Chen Yan; Shuling Wei; Liqi Luo; Yuhua Zhu; Lan Luo (Human Cell, 2026)

Enzyme immobilization on nanomaterials in food industry: current status and future perspectives - Lang Du; Yingzhuo Liang; Sifan Cui; Jianyang Wei; Jianqiao Liu; Shuling Zhang; Yuqing Zhang; Liya Zhou; Ying He; Li Ma; Jing Gao; Yanjun Jiang (Critical Reviews in Food Science and Nutrition, 2026)

Novel distributed parameter models for self-centering dual rocking core system with multiple rocking sections - Chunxue Dai; Shuling Hu; Wei Wang; M. Shahria Alam; Theodoros L. Karavasilis (Soil Dynamics and Earthquake Engineering, 2025)

Boosting methanogenesis in high-solids anaerobic digestion of corn straw by coupling hydrogen nanobubbles with biochar - Chuanfei Bian; Yiming Shi; Mao Du; Shuaishuai Ma; Shiyu Li; Hao Liu; Luyao Wei; Shuling Cao; Binshou Wang; Hongliang Wang; Wanbin Zhu (Journal of Environmental Chemical Engineering, 2025)

Phosphorylated Scrophularia ningpoensis polysaccharides mitigate oxidative stress and modulate immunity by regulating the gut microbiota in cyclophosphamide-treated mice - Lufen Huang; Jianan Wang; Litao Wang; Shuling Liu; Xinru Niu; Zhouwen Wu; Kexin Guo; Si Gong; Bowen Wei; Zhaochun Wang; Jianing Mi; Yufeng Liu; et al. (Food Bioscience, 2025)

Integration of machine learning and meta-analysis reveals the behaviors and mechanisms of antibiotic adsorption on microplastics - Shuangshuang Bi; Ruoying Wu; Xiang Liu; Peng Wei; Shuling Zhao; Xinru Ma; Enfeng Liu; Hongfeng Chen; Jinling Xu (Journal of Hazardous Materials, 2025)

Dose-dependent developmental fluoride exposure leads to neurotoxicity and impairs excitatory synapse development - Wenjin Qiu; Xiaoyu Wang; Shuling Zhang; Zhenting Zhang; Kaiju Zhang; Zhijuan Shao; Yubo Liu; Ruting Wei; Liangzhao Chu; Peng Luo (Archives of Toxicology, 2025)

Mechanochemical conversion of chitin to high-bioactivity oligomers of N-acetyl-D-glucosamine - Shuling Cao; Wanbin Zhu; Weichen Wang; Binshou Wang; Luyao Wei; Xufeng Yuan; Hongliang Wang (Carbohydrate Polymers, 2025)

Impacts of shale gas wastewater leaks on neighboring crops: Physiological and morphological responses of tomatoes - Fengming Li; Xulin Yu; Yushun Yang; Wei Tao; Mengting Zhu; Di Zhang; Shuling Shi; Huiqiang Li; Peng Tang; Alberto Tiraferri; Baicang Liu (Process Safety and Environmental Protection, 2025)

Moisture-absorbing expansion and cracking characteristics of central Sichuan red-bed mudstone based on digital speckle correlation method - Kang Huang; Zhangjun Dai; Shuling Huang; Fei Yu; Shichang Li; Kaiwen Tong; Wei Zhang; Shanxiong Chen (Bulletin of Engineering Geology and the Environment, 2025)

Spatio-temporal variations and influencing factors analysis of coastal wetlands in Tianjin, China - Shuling Yu; Maihemutijiang Mijiti; Min Song; Jingxuan Xu; Dongfang Yuan; Wei Xu (Regional Studies in Marine Science, 2024)

Gas charging and accumulation in deep coal measures of Daning-Jixian Block, Ordos Basin: insights from fluid inclusions and basin modeling - Zhanwei Li; Song Li; Dazhen Tang; Shuling Tang; Jiaosheng Yang; Wei Hou (Frontiers of Earth Science, 2024)

Unveiling the impacts of microplastic pollution on soil health: A comprehensive review - Nan Chang; Li Chen; Na Wang; Qingliang Cui; Tianyi Qiu; Shuling Zhao; Haoran He; Yi Zeng; Wei Dai; Chengjiao Duan; Linchuan Fang (Science of The Total Environment, 2024)

Effects of Taurine and Enzymatic Cottonseed Protein Concentrate Supplementation in Low-Fishmeal Diet on Growth, Liver Antioxidant Capacity, and Intestinal Health of Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Zhong Huang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2024)
This study was conducted to investigate the impacts of the dietary addition of taurine and enzymatic cottonseed protein concentrate (ECPC) in low-fishmeal diet on the growth performance, plasma biochemical indices, hepatic antioxidant capacity, intestinal anti-inflammatory capacity, intestinal microflora, and muscle quality of golden pompano (Trachinotus ovatus). A total of three isonitrogenous diets were given to 225 golden pompanos (5.6 ± 0.14 g). They were randomly divided into nine cages (1.0 m × 1.0 m × 1.5 m; three cages per treatment) with equal stocking numbers of twenty-five fish per cage. The results indicated that the CSM-TC group significantly increased the growth performance of juvenile T. ovatus (p

Effective and mechanistic insights into shale gas wastewater reverse osmosis concentrate treatment using ozonation-biological activated carbon process - Mengting Zhu; Peng Tang; Xulin Yu; Fengming Li; Shuling Shi; Di Zhang; Jialin Shi; Wei Tao; Xia Ruan; Lujian Liu; Baicang Liu (Science of The Total Environment, 2024)

Self-centering dual rocking core system with viscous dampers in additional rocking sections - Chunxue Dai; Shuling Hu; Wei Wang (Soil Dynamics and Earthquake Engineering, 2024)

Absorption, metabolism, bioactivity, and biotransformation of epigallocatechin gallate - Shuling Zhang; Bingyong Mao; Shumao Cui; Qiuxiang Zhang; Jianxin Zhao; Xin Tang; Wei Chen (Critical Reviews in Food Science and Nutrition, 2024)

Insights into the catalytic mechanism of V-Mo@CN for the oxidation of 5-hydroxymethylfurfural to 2,5-diformylfuran - Shibo Yang; Tong Sun; Xiaokai Li; Wenbo Liao; Jianfei Bian; Xing Tang; Shuling Yang; Lu Lin; Wei Jiang; Lincai Peng; Yong Sun (Chemical Engineering Journal, 2024)

Isoliquiritigenin retards starch digestion by increasing resistant starch content and inhibiting the activities of α-amylase and α-glucosidase - Yushi Wei; Le Deng; Shuling Chen; Xing Hu; Guowen Zhang (Food Bioscience, 2024)

Source-Specific Ecological Risk of Atmospheric PM2.5-Bound Metals and Implications for Air Pollution Control: A Regional Perspective from China - Weiwei Lin; Hedi Zhang; Yuming Lai; Shuling Zhuang; Qiannan Wei; Shaojie Fu; Dejian Mai; Luan Yuan; Qing Wei; Dingli Yue; Qiansheng Hu (Exposure and Health, 2024)

Role of antenatal anxiety in the relationship between maternal exposure to nitrogen dioxide and small for gestational age: A birth cohort study - Qiannan Wei; Weiwei Lin; Hedi Zhang; Yuming Lai; Shuling Zhuang; Zhenyan Han; Qingqing Wang; Lijie Wang; Wenzhuo Li; Li Wen; Hongying Hou; Qiansheng Hu (Science of The Total Environment, 2023)

Hybrid self-centering dual rocking core system for seismic resilience by controlling both structural and nonstructural damage - Shuling Hu; Ruibin Zhang; Wei Wang (Engineering Structures, 2023)

Probabilistic residual displacement-based design for enhancing seismic resilience of BRBFs using self-centering braces - Ruibin Zhang; Shuling Hu; Wei Wang (Engineering Structures, 2023)

The effects of prenatal PM2.5 oxidative potential exposure on feto-placental vascular resistance and fetal weight: A repeated-measures study - Weiwei Lin; Yuming Lai; Shuling Zhuang; Qiannan Wei; Hedi Zhang; Qiansheng Hu; Peng Cheng; Manman Zhang; Yuhong Zhai; Qingqing Wang; Zhenyan Han; Hongying Hou (Environmental Research, 2023)

Effects of Fermented Cottonseed Meal Substitution for Fish Meal on Intestinal Enzymatic Activity, Inflammatory and Physical-Barrier-Related Gene Expression, and Intestinal Microflora of Juvenile Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Jun Wang; Yun Wang; Zhong Huang; Wei Yu; Xiaolin Huang; Heizhao Lin; Maoyan Luo; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2023)
The present study was conducted to investigate the effects of dietary fermented cottonseed meal (FCSM) substitution for fish meal on intestinal enzymatic activity, inflammatory and physical-barrier-related gene expression, and intestinal microflora of juvenile golden pompano. The 375 golden pompanos were divided into 15 groups of 25 fish each, with three replicates for each experimental group. The fish were fed five experimental diets (0 (FM), 12.5% (CSM12.5), 25% (CSM25), 50% (CSM50), and 100% (CSM100) substitution levels) for 8 weeks. The fish were reared and fed the experimental diets under a natural-day light cycle. Compared with the control group, the activities of AMY (amylase) enzymes in the CSM12.5 group and all other groups were elevated (p

Performance improvement of flapping propulsions from spanwise bending on a low-aspect-ratio foil - Tianlong Lin; Wei Xia; Rosario Pecora; Kun Wang; Shuling Hu (Ocean Engineering, 2023)

Explainable machine learning models for probabilistic buckling stress prediction of steel shear panel dampers - Shuling Hu; Wei Wang; Yongchang Lu (Engineering Structures, 2023)

Life-cycle benefits estimation of self-centering building structures - Shuling Hu; Wei Wang; M. Shahria Alam; Ke Ke (Engineering Structures, 2023)

Synthesis of sodium alginate/phosphorus tetramethylmethyl sulfate biocomposite beads with exceptional adsorption rate for Cr(VI) removal - Shuling Liang; Weiquan Cai; Chengxiong Dang; Xiong Peng; Zhijia Luo; Xingchuan Wei (Journal of Environmental Chemical Engineering, 2023)

Differential effects of pore structure of mineral and maceral components on the methane adsorption capacity evolution of the lower jurassic Da'anzhai member of the Ziliujing Formation lacustrine shale, Sichuan Basin, China - Shuling Xiong; Zhiye Gao; Weihang Wei; Yaohua Wang (Marine and Petroleum Geology, 2023)

Hybrid test and numerical study of beam-through frame enhanced by friction spring-based self-centering rocking core - Ruibin Zhang; Wei Wang; Chengyu Yang; Shuling Hu; M. Shahria Alam (Engineering Structures, 2023)

Transcriptome analysis reveals the mechanisms of hepatic injury caused by long-term environmental exposure to atrazine in juvenile common carp (Cyprinus carpio L.) - Jingbo Liu; Guangcheng Yang; Yanxia Gao; Xinran Li; Yuting Long; Shuling Wei; Yuxin Zhao; Shanshan Sun; Shujuan Gao (Environmental Science and Pollution Research, 2022)

Identifying the Geography and Determinants of O2O Online Retailers in Megacity in Central China: A Case Study of Zhengzhou City - Jinghui Qi; Shuwen Niu; Chenxi Ye; Luojia Wang; Yongna Wei; Yuzhao Wen; Shuling Zhao (Chinese Geographical Science, 2021)

Patterns of variation of the major histocompatibility complex class IIB loci in Chinese goose (Anser Cygnoides) - Xu Zhou; Chunjin Li; Kangle Yi; Hongyan Liang; Lu Chen; Yanling Sun; Shuling Niu; Wei Wu (Immunogenetics, 2009)